ORGANOLOGI SERULING BAMBU PANGILO DESA KOTO LUA KERINCI PROVINSI JAMBI (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the organology of the Pangilo Bamboo Flute in Koto Lua Village, Kerinci Regency, Jambi Province, including instrument classification, shape and size, tools and materials, manufacturing process, playing techniques, songs, and their function in community life. This study used a qualitative descriptive method. Data was obtained through observation, interviews, documentation, literature review, and participant observation. Research informants included craftsmen, bamboo flute players, and residents. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that the Pangilo Bamboo Flute is a traditional musical instrument belonging to the edge-blown aerophone group. This instrument is made from tamiang bamboo and is traditionally crafted using simple tools such as saw, machete, sandpaper, iron, pencil, ruler, Styrofoam, sponge, and raffia rope. This instrument has an elongated shape with six tone holes and one blow hole. Playing techniques include sitting cross-legged, using proper finger placement, and using diaphragmatic breathing to produce a stable and clear sound. The songs played generally have themes of life, love, and longing, such as "Tumbuk Punano" and "Nurjani." Besides being a source of personal entertainment, the Pangilo Bamboo Flute also serves as an accompaniment to various traditional ceremonies, such as weddings, bathing ceremonies, circumcisions, tales, drums, and sko feasts. This research shows that the Pangilo Bamboo Flute has important cultural and organological value and therefore needs to be preserved as a cultural heritage of the Kerinci people.